Frequency of cannabis and amphetamine use past month in patients on opioid maintenance treatment with buprenorphine - Simonovska, Natasha; Velikj Stefanovska, Vesna; Bekarovski, Niko; Petkovska, Lidija; Pereska, Zanina; Babulovska, Aleksandra; Kostadinoski, Kristin; Biljana Ivanova (My University, 2024)
Background Maintenance treatment for opioid use disorder, either with methadone or buprenorphine-based medications, improves retention in the treatment and reduces abuse of illicit opioids. We aimed to examine the cannabis and amphetamine use before and while the treatment with buprenorphine, as well as the correlation of this findings with the demographic characteristics and duration of opioid use disorder. Methods This analytical cross-sectional study was implemented at the Skopje University Clinic for Toxicology. Participants diagnosed with opioid use disorder receiving pharmacological treatment buprenorphine, were asked to self-report the past month cannabis and amphetamine use. Specially for this study designed questionnaire adapted to the “treatment demand indicator” was used to collect the data. Results Тotal of 112 participants (88.39% male and 11.61% female) were enrolled. Before the buprenorphine treatment, cannabis use was permanent in 60 (53.57%), and periodic or not used in 52 (46.43%) participants, and amphetamine use was permanent in 40 (35.71%), and periodic or not used in 72 (64.29%) participants. After the buprenorphine treatment cannabis was not used or used occasionally by 71 (63.39%) of the participants, ones per week or less was used by 14 (12.50%), 2-6 days per week was used by 9 (8.04%), daily used by 6 (5.36%) and unknown by 12 (10.71%) participants, with not significant association with the gender (p=0.732). negative not significant correlation with the age (R=-0.011; p=0.951) and positive not significant correlation with the duration of opioid dependence (R=0.032; p=0.733). Amphetamine after the buprenorphine treatment was not used or used occasionally by 103 (91.96%) participants, used ones per week or less by 6 (5.36%) and 2-6 days per week by 3 (2.68%) participants with significant association of male gender with no use (p=0.009), negative not significant correlation with the age (R=-0.073; p=0.445) and positive not significant correlation with the duration of opioid dependence (R=0.027; p=0.774). Conclusions Before starting treatment of opioid use disorder with buprenorphine, more than half of the patients had a permanent use of cannabis, while more than a third use amphetamines. After initiation of buprenorphine treatment, although some of the patients occasionally use cannabis and amphetamines, the permanent use of these psychoactive substances is reduced.
Keywords: buprenorphine; cannabis; amphetamine; frequency